Weibull-Based Reliability of Full-Arch Zirconia Prostheses in a Mandibular All-on-4 Model: Monolithic Versus Titanium-Bar-Supported Designs - Tuzlali, Mesut; Baki, Nagehan; Avcu, Guler Yildirim; Bahce, Erkan (Mdpi, 2026)
Full-arch zirconia prostheses for mandibular All-on-4 rehabilitations are provided as screw-retained monolithic zirconia (Zr-Mono) or as a zirconia suprastructure luted to a CAD/CAM titanium bar (Zr-TiBar). Because zirconia is a brittle and flaw-sensitive ceramic, design assessment should incorporate stress-field-weighted fracture risk. This in silico study compared zirconia tensile stress, deformation, and Weibull-based reliability between Zr-Mono and Zr-TiBar designs in a standardized edentulous mandibular All-on-4 model (posterior implants tilted 30 degrees) using linear static finite element analysis. Accordingly, 300 N posterior unilateral loads were applied at the first molar (axial; 45 degrees oblique). Outcomes were maximum principal tensile stress in zirconia (S1max), total prosthesis deformation, and Weibull-predicted fracture probability (Pf) derived from the tensile S1 field. Under axial loading, S1max was essentially identical between designs (similar to 277 MPa). Under oblique loading, S1max was modestly lower for Zr-TiBar (similar to 227 MPa) than for Zr-Mono (similar to 234 MPa), and deformation was slightly lower for Zr-TiBar (<0.07 mm in all cases). Pf remained very low for both designs (10(-6)-10(-7) range) and differed only slightly between them. Under the modeled single 300 N posterior load case, the titanium-bar support reduced deformation and modestly reduced oblique-load peak tensile stress but did not materially reduce the predicted zirconia Pf compared with monolithic zirconia.
Keywords: All-on-4; mandibular full-arch prosthesis; monolithic zirconia; CAD/CAM titanium bar; finite element analysis; Weibull analysis; probability of fracture; tensile stress; implant-supported fixed prosthesis; zirconia reliability